1972
DOI: 10.3171/jns.1972.37.2.0233
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary spinal cord sarcoidosis

Abstract: A dorsal laminectomy was performed on a 68-year-old woman with an intramedullary mass lesion, ultimately diagnosed as sarcoidosis. This rare lesion of the spinal cord is presented with references to similar cases. KEY WORDS sarcoidosis intramedullary mass dorsal lamineetomy paraparesis 1. Neurosurg. / Volume 37 / August, 1972 Address reprint requests to"

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

1977
1977
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 15 publications
0
6
0
2
Order By: Relevance
“…In the case described by Banerjee and Hunt (1972 ) a black woman aged 36 presented with a four month history of symptoms and signs suggestive of a cervical cord tumour, a myelogram showing narrowing of the spinal canal at C 6-7 level, with widening of the cord; at laminectomy a gelatinous tumour was seen to this site, and as much as possible of it was removed and found to consist of granulomas with some central necrosis; there was some deterioration postoperatively and limited improvement on subsequent treatment with prednisone; outside the nervous system, other evidences of sarcoidosis were BHL and enlargement of lacrimal glands. Semins et al (1972) reported the case of a woman aged 68 with paraparesis shown by myelography to be due to an…”
Section: Spinal Cordmentioning
confidence: 99%
“…In the case described by Banerjee and Hunt (1972 ) a black woman aged 36 presented with a four month history of symptoms and signs suggestive of a cervical cord tumour, a myelogram showing narrowing of the spinal canal at C 6-7 level, with widening of the cord; at laminectomy a gelatinous tumour was seen to this site, and as much as possible of it was removed and found to consist of granulomas with some central necrosis; there was some deterioration postoperatively and limited improvement on subsequent treatment with prednisone; outside the nervous system, other evidences of sarcoidosis were BHL and enlargement of lacrimal glands. Semins et al (1972) reported the case of a woman aged 68 with paraparesis shown by myelography to be due to an…”
Section: Spinal Cordmentioning
confidence: 99%
“…In the pre-MRI literature several similar cases of sarcoidosis presenting as a spinal cord tumor have been described (Banerjee and Hunt, 1972;Semins et al, 1972;Snyder et al, 1976;Day and Sypert, 1977). Symptoms of systemic sarcoidosis preceded the onset of myelopathy in most cases.…”
Section: Sarcoidosismentioning
confidence: 99%
“…16,18,27 Sarcoid involvement of the spinal cord has been reported rarely. 10,[59][60][61][62] After the advent of MRI, spinal involvement has been verified more often. 25,58,63 The most typical clinical signs are paraparesis and tetraparesis.…”
Section: Central Nervous System Lesionsmentioning
confidence: 99%